PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN MATEMATIKA MATERI ARITMATIKA SOSIAL - Kuswadi, Firginia; Pesik, Anekke; Pitoy, Cori (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to determine the differences in student learning outcomes taught with the Problem Based Learning model and student learning outcomes taught with the Direct Instruction model on social arithmetic material. This study used a quasi-experimental method, with a research design of Posttest Only Control Group Design. The samples of this study were taken from 2 homogeneous and the same classes, class VIIA which consisted of 20 students as the experimental class and VIIB which consisted of 20 students as the control class. Research statistics were analyzed using t-test with tcount = 3.644 ttable value = 1.686 then H0 was rejected. Thus, it is concluded that the average learning outcomes of students who are taught using the Problem Based Learning (PBL) model are higher than the average learning outcomes of students who are taught using the Direct Instruction (DI) model on social arithmetic material.Keywords : Problem Based Learning Model, Sosial Arithmetic, Learning Outcomes